Wondershare Quiz Media Development in Learning Building Space Materials for Deaf Class X SMALB Students - Adinda Ayu Maharani; Yuliyati Yuliyati (Department of Special Education, 2020)
Students with hearing impairment (deaf) who have obstacles in processing mathematical concepts can experience this anxiety and fear, which causes them to dislike mathematics. The purpose of this research is to develop a game media of mathematics on geometry materials for tenth grade students with hearing impairment in high school special education. This research refers to the steps developed by Borg and Gall 1989 modified into 9 steps. The main field test subjects were 2 people with hearing impairment. The subjects of the operational field test were 12 people with hearing impairment. The results showed that multimedia according to content experts was very valid with a percentage of 87,5%. According to the media expert it was valid with a percentage of 76,67%, and the results of the SMALB teacher validation of 90,91% means very valid. The main field test is very valid with a percentage of 88,33%. The operational field test is very valid with a percentage of 85,83%. It was proven that 66,67% of the trial assessors considered the developed media to be very valid to use and the remaining 33.33% assessed that the developed media was valid to use